Patients’ perception of childbirth according to the delivery method: The experience in our clinic - Camelia Alexandroaia; Romina-Marina Sima; Oana-Denisa Bălălău; Gabriel Octavian Olaru; Liana Pleş (Journal of Mind and Medical Sciences, 2019)
Introduction: The aim of this study is to identify the way in which childbirth in general, and the delivery method in particular, influenced the maternal psychosocial status and the perception upon birth during postpartum. Material and method: We conducted a cohort type 2 prospective study. We included patients who had given birth at “Bucur” Maternity of Hospital “St. John” Bucharest from the 1st of January 2017 until the 1st of January 2018. Results: The majority of the patients (21.05%) who chose to give birth vaginally assigned the maximum degree (10) to the difficulty of birth. The patients who gave birth through cesarean section experienced the feeling of sadness in a higher percentage than those who gave birth vaginally (30.52% versus 21.05%). Among the patients who were in favor of having more children, 85.45% preferred the same delivery method. All the patients who gave birth vaginally wished to have other children using the same method, while 81.4% from the patients who gave birth through cesarean section were in favor of more children. Conclusion: The patients’ perception of childbirth was a subjective parameter. Further studies with standardized questionnaires should be applied for more reliable results.